PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA - Lubis, Khairunnisa Maisarah; Sinaga, Bornok (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
This Classroom Action Research was carried out in two cycles and aimed to improve the creative thinking skills of Bina Bersaudara Medan Private Junior High School students by using a project-based learning model. 26 students from Bina Bersaudara Private Junior High School in Medan who are in grades VIII-2 of this study. Original, fluent thinking, flexibility, and elaboration are the four stages involved in each cycle. The results of this study show that a learning model based on projects can be applied. The average score of students increased from 37.33 in the very low category to 68.29 in the1medium category and 87.18 in1the high category in the second cycle. Students' classical abilities also improved, with 17 students (65.4%) achieving complete in the first cycle.